Ultrastructural organization of alveolar macrophages during late development of experimental acute pancreatitis - Zaiats, Liubomyr; Pasichnyk, Olga; Zukow, Walery (Journal of Education, Health and Sport, 2024)
Background. Nowadays, acute pancreatitis continues to remain an actual problem both in surgery and in intensive care medicine. The aim of the work was to study the dynamics of ultrastructural changes of alveolar macrophages in the long-term development of experimental acute pancreatitis. Material and methods. The experiments were carried out on 62 white Wistar male rats weighing 180–220 g. The animals were divided into three groups: first — intact, second — control, third — experimental with a model of acute pancreatitis, which was reproduced by intraperitoneal administration of a 20% solution of L-arginine in a total dose of 5 g/kg at one-hour interval. The control group of animals was intraperitoneally injected with an equivalent dose of isotonic sodium chloride solution. All research were performed under sodium thiopental anesthesia at the rate of 60 mg/kg body weight. Lung tissue for electron microscopic examination was collected from the lower lobe of the left lung at 3–5 and 7 days. Pieces of lung tissue measuring 1×1×1 mm were fixed in a 2.5% glutaraldehyde solution, followed by additional fixation in a 1% osmium tetroxide solution. After dehydration, the material was poured into Epon-Araldite. Sections with a thickness of 20–50 nm obtained on “Tesla BS-490” ultramicrotome were studied in a PEM-125K electron microscope. Results. It was found that three days after the start of the study, significant heterogeneity of alveolar macrophages was observed in the alveolar lumen. Next to active phagocytic macrophage elements with dystrophic-destructive changes are determined. Continuation of the experiment (5 days) leads to the progression of submicroscopic changes in alveolar macrophages, which are most pronounced on the7 day of the study. Conclusion. Acute experimental pancreatitis is accompanied by pronounced changes in the ultrastructural structure of alveolar macrophages. The features and severity of structural changes in alveolar macrophages depends on the duration of arginine-induced acute pancreatitis.